Land Suitability Analysis for Marine Tourism on Kalimantung Island, Central Tapanuli Regency, North Sumatera Province, Indonesia - Muhammad Ridha Syafii Damanik; Eko Prasetya; Teguh Febri Sudarma (Universitas Negeri Medan, 2024)
This study aims to spatially analyze the marine ecotourism potential of Kalimantung Island based on the Tourist Suitability Index (TSI). The method used in this research is descriptive qualitative, where the analysis is done with a spatial approach. Data collection techniques used were measurement, observation, and interviews. The data analysis carried out in this study uses scoring techniques. Land suitability analysis is categorized into 4 (four) designations, namely (1) Beach Tourism for Recreation Category, (2) Marine Tourism for diving, (3) Marine Tourism for snorkeling, and (4) Marine Tourism for swimming and canoeing category. The results of this study indicate that the condition of coral reefs on Kalimantung Na Godang Island and Kalimantung Na Menek Island is included in the good category, with coral cover of 55.55% and 52.13 respectively. The Tourism Suitability Index (TCI) for the Recreation Category on Kalimantung Na Godang Island is categorized as suitable with a TSI of 69%. The Recreation TSI of Kalimantung Na Menek Island is categorized as Very Suitable with a Recreation TSI of 95%. The Tourism Suitability Index (TSI) for the Diving Category on Kalimantung Na Godang Island and Kalimantung Na Menek Island is included in the Very Suitable category with a TSI of 83%. The Tourism Suitability Index (TSI) of the Snorkeling Category on Kalimantung Na Godang Island is included in the suitable category with a TSI of 68%. The Recreation TSI of Kalimantung Na Menek Island is included in the Very Suitable category with a Recreation TSI of 75%. The Tourism Suitability Index (TSI) Swimming- Canoeing Category on Kalimantung Na Godang Island and Kalimantung Na Menek Island are included in the Very Suitable category with TSI of 76% and 87% respectively.This study aims to spatially analyze the marine ecotourism potential of Kalimantung Island based on the Tourist Suitability Index (TSI). The method used in this research is descriptive qualitative, where the analysis is done with a spatial approach. Data collection techniques used were measurement, observation, and interviews. The data analysis carried out in this study uses scoring techniques. Land suitability analysis is categorized into 4 (four) designations, namely (1) Beach Tourism for Recreation Category, (2) Marine Tourism for diving, (3) Marine Tourism for snorkeling, and (4) Marine Tourism for swimming and canoeing category. The results of this study indicate that the condition of coral reefs on Kalimantung Na Godang Island and Kalimantung Na Menek Island is included in the good category, with coral cover of 55.55% and 52.13 respectively. The Tourism Suitability Index (TCI) for the Recreation Category on Kalimantung Na Godang Island is categorized as suitable with a TSI of 69%. The Recreation TSI of Kalimantung Na Menek Island is categorized as Very Suitable with a Recreation TSI of 95%. The Tourism Suitability Index (TSI) for the Diving Category on Kalimantung Na Godang Island and Kalimantung Na Menek Island is included in the Very Suitable category with a TSI of 83%. The Tourism Suitability Index (TSI) of the Snorkeling Category on Kalimantung Na Godang Island is included in the suitable category with a TSI of 68%. The Recreation TSI of Kalimantung Na Menek Island is included in the Very Suitable category with a Recreation TSI of 75%. The Tourism Suitability Index (TSI) Swimming- Canoeing Category on Kalimantung Na Godang Island and Kalimantung Na Menek Island are included in the Very Suitable category with TSI of 76% and 87% respectively. Keywords: Spatial Analysis; Land Suitability; Region's Carrying Capacity; Marine Ecotourism